Solidago psammophila (Asteraceae: Astereae), a New Sand Dune Endemic Goldenrod from Northern Michigan, U.S.A. - Jess A. Peirson (The Great Lakes Botanist)
Solidago psammophila is described as a new species from open dune habitats along the southern shore of Lake Superior in Michigan’s Upper Peninsula. Field and herbarium studies revealed that it is endemic to the state of Michigan, restricted to an approximately 100 km section of shoreline from Grand Sable Dunes in the west to Whitefish Point in the east. This goldenrod is ecologically similar to S. gillmanii (A. Gray) Steele in Solidago subsect. Humiles (Rydb.) Semple, sharing apparent adaptations to the sand dune environment. However, it differs from S. gillmanii and other members of subsect. Humiles in its vegetative pubescence and lack of glutinosity. It is morphologically most similar to the widespread S. hispida Muhl. in subsect. Erectae (G. Don) Semple & J.B. Beck. DNA ploidy determinations from flow cytometry revealed that this newly described species is tetraploid, whereas S. hispida has been shown to be uniformly diploid across its range. Solidago psammophila appears to be an example of the interplay of polyploidy and habitat specialization leading to ecological speciation in the recently glaciated Great Lakes region. A brief discussion of the other Great Lakes region endemic goldenrods and a revised key to all Michigan Solidago species are included.